南洋与没有历史的人民 : 苗秀小说中的底层华人= Nanyang and the people without history: a study of the lower-class Chinese people in Miao Xiu's novels - 李泓诺 Li, Hongnuo (Nanyang Technological University, 2023)
1974年末，华文文艺界开始重视强调“马华文艺独特性”的口号，这标志着马华文学独立发展的开始，也是马华文学朝着本土意识转向的重要阶段。这一时期，文学作品逐渐脱离了纯粹唯美主义的范畴，开始“反映此时此地”，建立自己的独特性。新马本地作家苗秀也将自己的创作方向转向关注本土特色和现实生活。苗秀是一位怀有强烈道德观念和人道关怀的作家。他的长篇小说、中篇小说以及小说集，例如《火浪》、《新加坡屋顶下》、《边鼓》和《红雾》，均描绘了50年代英殖民统治下底层华人的艰辛生活以及新马沦陷期间人民在生活上的苦难。其中的人物包括抗日分子、扒手、私会党徒、妓女、茶花女和知识分子等。因此，可以理解的是，苗秀的创作基本是反映现实的，而这其中就包括了他所熟悉的底层阶级。本文将以苗秀的小说的代表，着重探讨阶级和性别对底层华人的压迫，以及底层华人的国族认同。关键词：苗秀；现实主义；底层；阶级；性别；国族认同 At the end of 1974, the Chinese Literary and Art association began to pay attention and re-emphasize the " Uniqueness of Malaysian Chinese Literature and Art". This marked the beginning of the independence of Malaysian Chinese literature, where authors started to write realist novels. During this period, literary works broke away from the traditional aestheticism writing and started to highlight a sense of locality within the context of Malaysia and Singapore, establishing their own uniqueness. As a realist writer in Singapore, Miao Xiu also shifted his creative direction to writing realist novels that focused on local characteristics. Miao Xiu is a writer with strong moral values and humanitarian concerns. His novels, novellas, and novel collections, depict the hardships of the lower-class Chinese characters under the British colonial rule in the 1950s and the pathetic life of people during World War II. The lower-class characters included the anti-Japanese fighters, pick pocketers, secret society members, prostitutes, and intellectuals. As Miao Xiu was influenced by his father and China authors such as Guo Moruo, his literary works reflect the reality, and this included the lower classes which he is more familiar with. Therefore, this paper would use Miao Xiu’s literary works as analytical representatives to analyse the gender and class oppressions faced by the lower-class Chinese people. Furthermore, it will also analyse the national identity of these people. Keywords: Miao Xiu; Realism; Subaltern; Class; Gender; National Identity